Evaluating a Skin Cancer Education Program for the Deaf Community - Harry, Kadie M. (2012)
Skin cancer is the most common, preventable, and treatable cancer, so public education has been a priority. Unfortunately, for the Deaf community, most skin cancer information is difficult to access, so tailored approaches are needed. Participants (N = 136) were randomly assigned to view either a skin cancer education video in American Sign Language (ASL) (n = 75) or an alternate video (n = 61). All participants completed skin cancer knowledge questionnaires at baseline, immediately post-intervention, and two-months post-intervention. Control group participants could then transfer to the experimental condition, using their two-month follow-up data as their baseline. Participants who saw the skin cancer video gained significantly more knowledge than control participants, demonstrating the video’s effectiveness in increasing skin cancer control knowledge. There was no difference between the original experimental group and the delayed intervention group on knowledge gains.